Experimental analysis of supplementary cementitious materials with glass fibers. (2020) - Kanamarlapudi, Lakshmisupriya; Jagarapu, Durga Chaitanya Kumar; Eluru, Arunakanthi
Abstract: The aim of the research analyses the durability of concrete by Portland cement, silica fume (SF) & ground granulated blast furnace (GGBS). Here, mineral admixtures like GGBS and Silica fume are partially replaced with cement in concrete. Silica fume and GGBS are replaced with varying proportions of 0, 10, 20, 30%. Here, M40 grade of concrete is used for mix design and 0.5% of Alkali resistant (AR) type Glass fibers are also added to the total volume of the concrete. The present article investigates the detailed study of split tensile, bending, compressive strength of the concrete and comparing is done with control concrete.